Over view of Complexity in Cryogenic Instrumentation System - P. Chandrasekar, Dr.; Kannan, V. (International Journal of Engineering and Technology, 2018)
Cryo meaning icy cold. The suffix 'genics' stands for science. It is defined as the science and technology of temperatures below 120 K. The Cryogenic liquids are used in various fields like medicine, super conducting technology, rocketry etc.Â The cryogenic propellants Liquid Hydrogen as fuel and Liquid Oxygen as oxidizer are preferred in launch vehicles due to its very high specific impulse and these propellants are very hazardous. This paper explains the properties of the cryogenic propellants and required instrumentation for achieving the safe handling and to meet the accuracy in measurements.Â Â